Legal Approach to International Cooperation on Cloud Storage of Personal Information - Zhang, Yi (Technium Social Sciences Journal, 2023)
The development of information technology has accelerated the process of globalization and has also internationalized the issue of personal information storage and protection. Personal information can be stored in a cross-border cloud based on the development of Internet technology. However, the separation of the controlling place and the storage place of personal information has brought new challenges to the international regulation of personal information protection. For example, the conflict of legislation, law enforcement, judicial jurisdiction, and the exercise of cyber sovereignty between different countries, etc. In order to strengthen international cooperation on the safety of personal information, it is recommended to promote the sharing of cloud storage of personal information by establishing international self-regulatory organizations, constructing a safety line for the protection of the private rights of information, creating the principle of confirming interests before the usage of information and strengthening the mechanism of punitive compensation in malicious commercial use, etc. It is important to further improve domestic unified legislation and clarify the extraterritorial effects of domestic laws. And introduce data controller standards under the principle of international comity to break the inherent territorial jurisdiction principle. Besides, it is also very necessary to establish and improve the graded and classified management and early warning mechanism for the commercial use of personal information stored abroad. Finally, it is important to take an active part in international negotiations and strive for the right to make international rules on personal information protection.